Tradition in the system of transition. Chekhov at the turn of the ages - Силантьева, Валентина Ивановна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The article raises the question of specific peculiarities of tradition inheritance in periods of «the turn of the ages» and transition from one form of artistic world reflection to the other. As experience has shown, the questions of artistic consciousness transition occur periodically; in the literature of our time, it is vividly demonstrated by postmodern consciousness. To characterize such unstable periods, synergetic terminology and its concept list are used. Thus the articles and scientific works use the notions of “non-equilibrium”, “dissipation”, “entropy”. Hence we can assume that in turbulence situation and in the context of Chaos triumph, the alteration of tradition assimilation forms new perspective on the achievements of the predecessors. The paper proposes a new scheme that is aimed to analyze the works created in the transitional era. The study of Chekhov’s work becomes the starting point of our investigation. The research sees Chekhov as a writer who united the XIX-th and the XX-th centuries in literature. His attitude to the problem of assimilation and rethinking of the past is shown. The writer’s attitude towards tradition becomes a high-priority problem. Chekhov’s letters are used alongside with his polemic against Tolstoy about the novel «Resurrection» as the material of analysis. Theoretical basis of the research is provided by Lotman’s works comprising the «bang» theory; and moreover by R. Arnheim’s and M. Wertheimer’s Gestalt theory. Solovyov’s work on questions of «unity», as his philosophical doctrine, determines the pattern of chaos and turbulent development of life and art. Synergetic paradigm of transition from disintegration and chaos to stability is represented by works of H. Haken, I. Prigogine and their followers. Issues of artistic reorientation in the art of the late XIX–XX centuries and Chekhov’s place in the literature of his time were treated by Andrey Beliy and D. Merezhkovskiy, so the article registered their thoughts, utterances and conversations with Chekhov on this topic. Chekhovs “transitional place” in the art of the turn of the XX th century is being dwelled upon for a long time. Chekhov’s place in literature of the time was considered by Andrey Beliy and D. Merezhkovskiy. During the XX th century this issue was brought up not once but it is “the theory of transition” that at the turn of the XXI st century shed light on Chekhov’s heritage. Analyzing the problem outlined above, the author concludes, that tradition at the moments of «transitional time» is treated mostly as an object of ridicule and denial. Some prefer to refuse it but not correct according to time demands. Many authors see tradition as an object to active experiments. Thus the factor of «progressive randomness» comes into force. As a result of such actions the new long-lasting genres appear. This is what happened to Chekhov: he created the prose and drama, which surprised his contemporaries and provoked their anger, but these works have survived in the ХХ th century and continue to live in the XXI st century.